Peningkatan Proses Pembelajaran Tematik Menggunakan Media Animasi di Kelas III SDN 01 Pakan Rabaa Solok Selatan - Afrimon , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Afrimon, 2013 The Grow Thematic Learn Proses User by Media Animation at Grade 3 rd Primary School 01 Pakan Rabaa South Solok Regency. A Thematic learns proses at grade 3 rd in primary school 01 Pakan Rabaa South Solok Regency is not with pratical in from present right now study link by teacher centered talked handel and conception without, take indication unused thematic learn.The end action resultan it claship are to take steps thematic proses with use animation subjek. For goal ship contact classmate its to growth tematic on animation acceording Suharsimi need four stepline, the are to a. plannering, b. acting, c. observing, and d. reflecting. Resource subject in grade 3 rd pupils at primary school 01 Pakan Rabaa South Solok Regency a mount 22 persons. A resert instrument is observasi sheet leaf recordly learn and documentasi notes. Record anicosus papers to prepare ol all data form will be collected, reduction rine to include activity and clarilocation and so that summary and didescraption, its progress to use animasi media form grow up learn prosesing work team to pupil in grade 3 rd primary school 01 Pakan Rabaa South Solok Regency. At finally will be born learn plant packed animasi media. More activity some student in study proses an more goals learn in part al subject with group.